2021
DOI: 10.1097/md.0000000000025815
|View full text |Cite
|
Sign up to set email alerts
|

Modified Glasgow coma scale for predicting outcome after subarachnoid hemorrhage surgery

Abstract: There are many grading scales that attempt to predict outcome following aneurysmal subarachnoid hemorrhage (aSAH). Most scales used to assess outcome are based on the neurological status of the patient. Here, we propose a new scale for aSAH patients that combines the Glasgow Coma Scale (GCS) and the modified Fisher scale (mFS). Five hundred ninety-seven patients with aSAH who were treated at our institution between January 2008 and December 2017 were retrospectively analyzed. Initial GCS score, Hunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Bae et al discovered a mean age of 55.9 ± 11.5 years, which is similar to our finding and, unlike Nguyen et al, has no significant role as a predictor of clinical outcome [20,22]. Similarly, Bae et al discovered that 40% of the patients had hypertension and 7.5% had diabetes, which is comparable to our demographic findings.…”
Section: Discussionsupporting
confidence: 90%
“…Bae et al discovered a mean age of 55.9 ± 11.5 years, which is similar to our finding and, unlike Nguyen et al, has no significant role as a predictor of clinical outcome [20,22]. Similarly, Bae et al discovered that 40% of the patients had hypertension and 7.5% had diabetes, which is comparable to our demographic findings.…”
Section: Discussionsupporting
confidence: 90%
“…The inclusion criteria for the patients were as follows: (1) age ≥10 years old; (2) Hunt-Hess grades I-V; (3) spontaneous SAH was confirmed by imaging examination or lumbar puncture; (4) intracranial aneurysm was confirmed by DSA and the aneurysm resulted in SAH; and (5) the family of the patient signed the informed consent and cooperated with the clinical treatment and follow-up. The exclusion criteria were as follows: (1) the patient with aSAH did not undergo NSE examination; (2) previous intracranial aneurysms were treated by clipping or embolization; (3) diagnosis of intracranial aneurysm was unclear; (4) intracerebral hematoma unrelated to the offending aneurysm; (5) the patient was expected to live for less than 1 year due to severe cooccurrence of other systemic diseases; and (6) pregnant or nursing women.…”
Section: Study Population and Datamentioning
confidence: 99%
“…Identifying and quantifying the severity of brain injury to predict prognosis as early as possible are major challenges at present. Initial clinical status determined by Glasgow coma scale (GCS) and Hunt-Hess grade has been associated with prognosis [2,3]. However, an accurate and direct clinical indicator that can predict the prognosis of patients with aSAH is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 31 Likewise, the score is also widely used by neurosurgeons for the initial assessment of patients with SAH, with higher scores indicating a lower level of consciousness impairment. 32 Studies by Zheng et al 16 and Ma et al 17 then found that the GCS score was significantly higher in the nimodipine combination therapy group of SAH patients after treatment. In the present study, we found that the GCS score of patients in the nimodipine-treated group were significantly higher than those in the control group.…”
Section: Discussionmentioning
confidence: 92%